Prototype Kontrol Dan Monitoring Air Tandon Berbasis Mikrokontroler - Wati, Hera; Riyanto, Agus; Mardianto, Eko; Syamsudin, Mariana; Rahayu, Wiwit Indah (Electrical Network Systems and Sources, 2025)
The availability of clean water is important for health, but not all areas have adequate access. Some communities rely on rainwater, wells, or unsuitable ditches for their daily needs. To overcome this problem, a microcontroller-based water tank control and monitoring system was developed near water sources such as ponds or ditches. This system uses simple filtration with silica sand, zeolite stone, activated carbon, coral shell sand, and coconut fiber to filter dirty water into clean water. The filtration results showed an increase in water quality: the pH of clean water increased from 6.39 to 8.18 and the TDS decreased from 0.63 to 0.03. Pond water increased in pH from 7.22 to 8.19, with TDS decreasing from 0.61 to 0.43. Ditch water showed an increase in pH from 6.97 to 7.77, but a slight increase in TDS from 0.80 to 0.85. Overall, this filtration improves water quality by adjusting pH and reducing TDS.